Characterizing a Preclinical Magnetic Particle Imaging System With Separate Pickup Coil - Wells, James; Paysen, Hendrik; Kosch, Olaf; Loewa, Norbert; Schmitzberger, Florian; Makowksi, Marcus; Franke, Jochen; Trahms, Lutz; Wiekhorst, Frank (IEEE Transactions on Magnetics, 2017)
Magnetic particle imaging (MPI) is an emerging technology with the potential for great impact on both medicine and biomedical research. Its optimization and acceptance are dependent upon a significant research effort in the development of tracer materials, data acquisition equipment, and image reconstruction techniques. We present initial results obtained from a prototype signal acquisition instrument designed to offer improvements to the sensitivity, and signal-to-noise ratio (SNR), of a preclinical MPI system (Bruker 25/20). We present the Fourier analysis of the signals detected using both the original data collection instrument provided with the MPI system, and the new prototype detector. By comparison of the spectra obtained, we show that the imaging signals from the prototype instrument are of greater intensity, and extend into higher frequencies, than those obtained using the original measurement instrument. We present image reconstructions of vascular phantoms containing tracer at concentrations between c(Fe) = 0.1 and 0.0125 mol/L. The improved sensitivity of the prototype detector allows the resolution of phantoms at tracer concentrations below those attainable using the original detector instrument. Finally, we quantify the improvement offered by the new detector based on a summation of the SNR values above a background threshold, within the frequency region of interest for MPI data acquisition. By plotting these totals at a variety of sample concentrations, we calculate a final receive gain (FRG) factor to describe the improvement offered by the new detector. For the prototype studied, we find FRG = 4.7 ± 0.6.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Image reconstruction; magnetic particle imaging (MPI); magnetic particle spectrometry; medical imaging